Bridging Social Capital through Modern Educational Governance: A Sociological Analysis of Stakeholder Collaboration in Digital Learning Environments - Rawis, Joulanda A.M.; Sumilat, Meiny Conny (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2025)
This study explores the role of social capital in bridging stakeholder collaboration through modern educational governance in digital learning environments The aim is to examine how social capital fosters trust facilitates stakeholder collaboration and addresses the digital divide in digital education settings A qualitative approach was employed using a literature study to analyze existing research on social capital governance models and digital learning environments Findings indicate that trust built through social capital is critical for effective collaboration among stakeholders in digital education Additionally governance models that prioritize inclusivity and participation enhance stakeholder collaboration and the development of social capital The study also identifies the challenges posed by the digital divide and emphasizes the need for equitable access to technology and digital literacy programs The research suggests that governance models should integrate strategies for overcoming the digital divide ensuring that all stakeholders regardless of their socio economic background can engage fully in digital learning By addressing these issues educational governance can foster sustainable collaborative and inclusive digital learning environments that leverage social capital for educational success < p>